Genotypic Effects of Fertilization on Seedling Sweetgum Biomass Allocation, N Uptake, and N Use Efficiency - Scott X. Chang; Daniel J. Robison (The Scientific World Journal)
Screening and selecting tree genotypes that are responsive to N additions and that have high nutrient use efficiencies can provide better genetic material for short-rotation plantation establishment. A pot experiment was conducted to test the hypotheses that (1) sweetgum (Liquidambar styraciflua L.) families have different patterns in biomass production and allocation, N uptake, and N use efficiency (NUE), because of their differences in growth strategies, and (2) sweetgum families that are more responsive to N additions will also have greater nutrient use efficiencies. Seedlings from two half-sib families (F10022 and F10023) that were known to have contrasting responses to fertility and other stress treatments were used for an experiment with two levels of N (0 vs. 100 kg N/ha equivalent) and two levels of P (0 vs. 50 kg P/ha equivalent) in a split-plot design. Sweetgum seedlings responded to N and P treatments rapidly, with increases in both size and biomass production, and those responses were greater with F10023 than with F10022. Growth response to N application was particularly strong. N and P application increased the proportional allocation of biomass to leaves. Under increased N supply, P application increased foliar N concentration and content, as well as total N uptake by the seedlings. However, NUE was decreased by N addition and was higher in F10023 than in F10022 when P was not limiting. A better understanding of genotype by fertility interactions is important in selecting genotypes for specific site conditions and for optimizing nutrient use in forestry production.